2012
DOI: 10.1016/j.adolescence.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Participating in a policy debate program and academic achievement among at‐risk adolescents in an urban public school district: 1997–2007

Abstract: This study investigates the relationship between participating in a high school debate program on college‐readiness in the Chicago Public School district over a 10‐year period. At‐risk school students were identified using an index including 8th grade achievement, poverty status, and enrollment in special education. Regression analyses were used to assess the association between debate participation and graduation and ACT performance. Overall, debaters were 3.1 times more likely to graduate from high school (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Her analysis showed that students participating in the debate activity had a 70% greater chance of graduating high school than their non-debating counterparts did (Mezuk, 2009). This study also found that students participating in the Chicago Urban Debate League had higher cumulative grade point averages and reading comprehension scores than their non-debating equivalents did (see also Anderson and Mezuk, 2012; Mezuk et al, 2011). Shackelford et al (2019) built on Mezuk’s (2009) study to show that students who competed in the Chicago Urban Debate League from 1997 to 2007 were also more likely to enroll in 4 year colleges than non-debaters.…”
Section: Debate and The Promotion Of Academic Growth In Educational Smentioning
confidence: 62%
“…Her analysis showed that students participating in the debate activity had a 70% greater chance of graduating high school than their non-debating counterparts did (Mezuk, 2009). This study also found that students participating in the Chicago Urban Debate League had higher cumulative grade point averages and reading comprehension scores than their non-debating equivalents did (see also Anderson and Mezuk, 2012; Mezuk et al, 2011). Shackelford et al (2019) built on Mezuk’s (2009) study to show that students who competed in the Chicago Urban Debate League from 1997 to 2007 were also more likely to enroll in 4 year colleges than non-debaters.…”
Section: Debate and The Promotion Of Academic Growth In Educational Smentioning
confidence: 62%
“…The National Association of Urban Debate Leagues (NAUDL) articulates its vision as: "All urban youth graduate from high school prepared to succeed in college and their careers and to contribute to their communities" [National Association of Urban Debate Leagues (NAUDL), 2019]. In turn, scholarship about Urban Debate League (UDL) programs has focused on the ways that debate positively impacts the grades, attendance, academic achievement and college trajectory of participating students that some researchers have labeled "at-risk" (Anderson and Mezuk, 2012;Shackelford, 2019).…”
Section: Neoliberal Narrative Of Debatementioning
confidence: 99%
“…Evidence from both qualitative and quantitative studies show that debate participation teaches both critical thinking cognitive skills and potentially NCS (Cridland-Hughes, 2012; Davis et al, 2016;Fine, 2010). Moreover, debate participation has been positively associated with positive achievement outcomes including likelihood of graduating high school, performance on college entrance exams, logical reasoning and literacy, and civic engagement and advocacy (Anderson and Mezuk, 2012;Mezuk, 2009;Mezuk et al, 2011;Mirra et al, 2016). Debate clubs are offered in middle and high schools, including in lower-resource urban districts like Chicago Public Schools.…”
Section: Introductionmentioning
confidence: 99%